Biochemical Markers and Enzyme Assays for Herbicide Mode of Action and Resistance Studies. Issue Volume 63: Issue SP1(2015) (February 2015) - Dayan, Franck E.; Owens, Daniel K.; Corniani, Natalia; Silva, Ferdinando Marcos Lima; Watson, Susan B.; Howell, J'Lynn; Shaner, Dale L.
Abstract : Herbicides inhibit biochemical and physiological processes or both with lethal consequences. The target sites of these small molecules are usually enzymes involved in primary metabolic pathways or proteins carrying out essential physiological functions. Herbicides tend to be highly specific for their respective target sites and have served as tools to study these physiological and biochemical processes in plants (Dayan et al. 2010b).